2012
DOI: 10.5402/2012/679619
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations in Patients with Chronic Kidney Disease on Maintenance Hemodialysis

Abstract: Cutaneous disorders can precede or follow the initiation of hemodialysis treatment. We evaluated the prevalence of various dermatological manifestations in patients undergoing hemodialysis at least twice a week for minimum of three months at our center. Patients were excluded if they were undergoing hemodialysis less than twice a week or on hemodialysis secondary to ESRD following graft dysfunction. One hundred and forty-three patients were evaluated. Among them, there were 113 male and 30 females. Among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 7 publications
5
26
1
7
Order By: Relevance
“…However, we observed it only in 17%. 10,11 Frequency as low as 8% has also been reported by Pico et al 3 Perforating disorders, combining the characteristics of Kyrles disease and perforating folliculitis can be found in CRF and diabetes mellitus. In our study this finding was observed in 7.5% of the patients of the patients, while Kolla et al reported a prevalence of 6.9%.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…However, we observed it only in 17%. 10,11 Frequency as low as 8% has also been reported by Pico et al 3 Perforating disorders, combining the characteristics of Kyrles disease and perforating folliculitis can be found in CRF and diabetes mellitus. In our study this finding was observed in 7.5% of the patients of the patients, while Kolla et al reported a prevalence of 6.9%.…”
Section: Discussionmentioning
confidence: 75%
“…Hajheydari et al, reported hair changes in 38% of the patients in their study. 10 Udaykumar et al reported hair changes in 27% of their patients. 12 Mucosal changes are common in patients with CKD and can be due to dehydration, mouth breathing, high concentration of urea and failure to breakdown to ammonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperpigmentation was seen in 30 (25%) patientswhich was similar to various other studies 11 . Failure of the kidneys to secrete beta-melano-stimulating hormone resulting in increased deposition of melanin in the skin has been implicated for this 12 . Pallor was seen in 20 (16.6%) of the patients and all these patients had a hemoglobin <6gm/dl.…”
Section: Discussionmentioning
confidence: 99%